2020
DOI: 10.1038/s41598-020-60041-2
|View full text |Cite|
|
Sign up to set email alerts
|

Local transplantation of adipose-derived stem cells has a significant therapeutic effect in a mouse model of rheumatoid arthritis

Abstract: Adipose-derived stem cells (ADSCs) have anti-inflammatory and regenerative properties. The purpose of this study was to investigate the effect of locally administered ADSCs in a rheumatoid arthritis (RA) mouse model. In an in vivo experiment, single-cell ADScs and three dimensionally-cultured ADSc spheroids were injected intra-articularly into the knees of RA model mice and histologically assessed. Marked improvement of synovial inflammation and articular cartilage regeneration was found in ADSCtreated mice. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…It is known that MSCs secrete anti-inflammatory cytokines (IL-10, TGF-α, IDO, TSG-6, etc.) [15][16][17]31], and we have confirmed that MSC CellSaics secreted 3.1-fold more anti-inflammatory cytokine TSG-6 in response to concentration of inflammatory cytokine TNF-α than the MSC spheroids [20]. In reference [34], it is reported that transplantation of ALG-PLO microencapsulated islets trigger inflammation by increasing the TNF-α concentration at the transplantation site.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It is known that MSCs secrete anti-inflammatory cytokines (IL-10, TGF-α, IDO, TSG-6, etc.) [15][16][17]31], and we have confirmed that MSC CellSaics secreted 3.1-fold more anti-inflammatory cytokine TSG-6 in response to concentration of inflammatory cytokine TNF-α than the MSC spheroids [20]. In reference [34], it is reported that transplantation of ALG-PLO microencapsulated islets trigger inflammation by increasing the TNF-α concentration at the transplantation site.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast to spheroids, the spaces between the petaloid RCP pieces of the CellSaic allow for the sufficient penetration of substances into the cells, which effectively prevents cell death [13]. Mesenchymal stem cells (MSCs) are promising options as the cells comprising CellSaics for subcutaneous transplantation since they have revascularization, anti-inflammatory, and immunomodulatory abilities [14][15][16][17] and are known to enhance islet function when co-transplanted with them [18,19]. Our previous study demonstrated the continuous release of angiogenic factors and anti-inflammatory cytokines via a combination of MSCs and CellSaics (MSC CellSaics) [13,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, depending on the underlying disease condition of a given patient, BMSCs may not be viable due to the risk of access or poor cell viability. Adipose tissue has been actively investigated as a promising treatment for incurable disorders (10)(11)(12)(13). ADSC therapy exhibits therapeutic effects on neurodegenerative disorders, cardiac injuries, and cutaneous damage.…”
Section: Discussionmentioning
confidence: 99%
“…Its immunosuppressive capacities are not yet fully elucidated. Nevertheless, it was noted that an ASCs' application decreased migration and proliferation of inflammatory cells, promoted the expression of anti-inflammatory cells, and downregulated the synthesis of proinflammatory cytokines, in laboratory models [70,71] The regenerative properties of ASCs have also been examined in rotator cuff repair models [72][73][74][75][76]. It has been noted that the local application of ASCs could result in less pronounced inflammation and increased bone mineral density in histologically evaluated tissues or improved their biomechanical function [72][73][74].…”
Section: Animal Modelsmentioning
confidence: 99%